FUSED PYRIMIDINES: PART-I: SYNTHESIS OF IMIDAZO[1,2-a]THIENO[2,3-d]- PYRIMIDIN-5(1H)- IMINE AND PYRIMIDO[1,2-a] THIENO[2,3-d] PYRIMIDIN-6-IMINE (Biological Sciences - PJSIR, 2004)
Annelating reagents, 2-(methylthio)-2-imidazoline (2) and 1,4,5,6-tetrahydro-2-methylthiopyrimidine (4) were prepared from 1,2-diaminoethane and 1,3-diaminopropane via 2-imidazolidinethione and 1,4,5,6-tetrahydropyrimidin-2-thione respectively. The substrate, 2-amino-4,-5-dimethylthiophen-3-carbonitrile (5) was prepared from butanone. The reaction of substrate (5) with the annelating reagents,( 2) and (4), in HMPT led to 2,3-dihydro-6,7-dimethylimidazo[1,2-a]thieno[2,3- d]pyrimidin-5(1H)-imine (6) and 1,2,3,4-tetrahydro-7,8-dimethylpyrimido[1,2-a]thieno[2,3-d]pyrimidin-6-imine (7) in good yields.